Applying real-time pricing for wind curtailment scenario using D2RD module of TOOCC - Teixeira, Brígida (2021)
Multi-agent systems are widely used tools to simulate and study the energy sector because of their distributed architecture. There are several simulator tools available in literature, however, much of these prove to be very domain specific. The emergence of the Tools Control Center tool allows these simulators to cooperate in order to solve more comprehensive problems and more complex scenarios. This paper presents a module of this tool known as Demand Response Registration Digital, which allows the study of the model and programs of Demand Response. To understand the operation of this module, an example is given considering a wind curtailment scenario.